Collaborative governance in increasing the competitiveness of Micro Small Medium Enterprises (MSMEs) through the Jakpreneur program - Alif Salsabila Katya; Saraswati Saraswati (Monas: Jurnal Inovasi Aparatur, 2021)
Based on the 2016 Economic Census, the number of businesses in DKI Jakarta has reached more than one million businesses, or 98.78%. The potential of MSMEs is able to reduce the unemployment rate and can drive the wheels of the Indonesian economy and DKI Jakarta specifically. However, in the current conditions, MSMEs in DKI Jakarta still have many limitations in terms of management and empowerment. Therefore, the DKI Jakarta Provincial Government created the JakPreneur Program to help MSMEs advance to class to be competitive and maintain their business. The DKI Jakarta Provincial Government embraces stakeholders to collaborate in developing the JakPreneur Program. The purpose of this study is to describe precisely the process and form of collaboration through the approach of collaborative governance in the JakPreneur Program and provide recommendations for program improvement. This study used a post-positivist approach with a qualitative method through interviews and literature study. The results of this study indicate that the collaboration process takes place effectively between the relevant stakeholders. The collaboration formed in this context is represented by implementing a number of activities from the P1-P7 stages of the JakPreneur program.